Bleeding Time Profile Using the Duke Method in Type 2 Diabetes Mellitus Patients at Telaga Dewa Public Health Center, Bengkulu - Tedy Febriyanto; Guntur Baruara; Jon Farizal; Putri Welkriana; Lidya Elvaretta (Jurnal Fatmawati Laboratory & Medical Science, 2026)
Background : Type II Diabetes Mellitus is a chronic metabolic disease characterized by hyperglycemia caused by impaired insulin secretion or insulin resistance. Chronic hyperglycemia may lead to various complications, including hemostatic disorders affecting bleeding time. The bleeding time examination using the Duke method is an important parameter in evaluating primary hemostatic function. This study aimed to analyze the bleeding time profile among patients with Type II Diabetes Mellitus at Telaga Dewa Public Health Center, Bengkulu City. Methods :This study used a descriptive cross-sectional design. The population consisted of all Type II Diabetes Mellitus patients at Telaga Dewa Public Health Center, totaling 55 individuals. A total of 31 respondents were selected using accidental sampling techniques. Data collection was conducted using questionnaires and bleeding time measurements on capillary vessels employing the Duke method. Data were analyzed univariately and presented in frequency distribution tables and percentages. Results : The results showed that the average bleeding time among Type II Diabetes Mellitus patients was 1 minute and 24 seconds. Most respondents (71%) had normal bleeding times (1–3 minutes), while nearly 29% experienced shortened bleeding times. No respondents were found to have prolonged bleeding times. Conclusion : The average bleeding time among Type II Diabetes Mellitus patients at Telaga Dewa Public Health Center was 1 minute and 24 seconds. Nearly one-third of respondents experienced shortened bleeding times. These findings indicate the importance of routine monitoring of the coagulation system in patients with Type II Diabetes Mellitus to prevent thrombotic complications. Therefore, periodic bleeding time examinations are recommended.